Adiponectin, IGFBP-1 and -2 are independent predictors in forecasting prediabetes and type 2 diabetes - Brismar, Kerstin; Hilding, Agneta; Ansurudeen, Ishrath; Flyvbjerg, Allan; Frystyk, Jan; Östenson, Claes-Göran (Frontiers in Endocrinology, 2023)
Objective: Adiponectin and insulin-like growth factor (IGF) binding proteins IGFBP-1 and IGFBP-2 are biomarkers of insulin sensitivity. IGFBP-1 reflects insulin sensitivity in the liver, adiponectin in adipose tissue and IGFBP-2 in both tissues. Here, we study the power of these biomarkers, IGF-I and IGF-II in predicting prediabetes and type 2 diabetes (T2D) in men and women with normal oral glucose tolerance (NGT). Design: Subjects with NGT (35-56 years) recruited during 1992-1998 were re-investigated 8-10 years later. In a nested case control study, subjects progressing to prediabetes (133 women, 164 men) or to T2D (55 women, 98 men) were compared with age and sex matched NGT controls (200 women and 277 men). Methods: The evaluation included questionnaires, health status, anthropometry, biochemistry and oral glucose tolerance test. Results: After adjustment, the lowest quartile of adiponectin, IGFBP-1 and IGFBP-2 associated independently with future abnormal glucose tolerance (AGT) in both genders in multivariate analyses. High IGFs predicted weakly AGT in women. In women, low IGFBP-2 was the strongest predictor for prediabetes (OR:7.5), and low adiponectin for T2D (OR:29.4). In men, low IGFBP-1 was the strongest predictor for both prediabetes (OR:13.4) and T2D (OR:14.9). When adiponectin, IGFBP-1 and IGFBP-2 were combined, the ROC-AUC reached 0.87 for women and 0.79 for men, higher than for BMI alone. Conclusion: Differences were observed comparing adipocyte- and hepatocyte-derived biomarkers in forecasting AGT in NGT subjects. In women the strongest predictor for T2D was adiponectin and in men IGFBP-1, and for prediabetes IGFBP-2 in women and IGFBP-1 in men.